LAPAROSCOPIC CHOLECYSTECTOMY: EXPERIENCE AT A TERTIARY LEVEL HOSPITAL - Sajid, Muhammad Tanveer; Hussain, Syed Mukarram; Bashir, Riaz Anwar; Mustafa, Quratul Ain; Ahmed, Muhammad; Halim, Abdul; Shukr, Irfan; Ahmed, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Cholecystectomy is the most frequently performed abdominal operation and currently laparoscopic cholecystectomy (LC) is considered gold standard being performed in 90% cases of symptomatic gallstones in USA since 1992. The aim of the study was to determine results obtained with LC at our setup. Methods: This observational case series study was conducted in department of General Surgery, Combined Military Hospital, Rawalpindi, from August 2009 to August 2011. The study participants were patients of both gender aged 14-75 years undergoing LC. Surgery was performed by consultant as well as resident surgeon. Demographic variables, intraoperative findings, mean operation time, hospital stay, conversion rate, morbidity and mortality were evaluated. Factors influencing rate of conversion were also studied. Results: A total of 504 patients were included. Mean age was 42.64 years (range 14-75 years) with a female: male ratio of 3.9:1.2. Comorbidities were found in 36.7% patients. Main indication of surgery was symptomatic cholelithiasis (78.57%). Mean operative time was 40.1±6.9 minutes which increased to 75.12±8.9 minutes in converted cases (p-value .000). Mean hospital stay was 1.89±1.1 days that significantly increased in converted cases (5.7±1.6 days) (p-value .000). Major surgical complications occurred in 3.17% patients. Common bile duct injury (CBDI) was found in 04 cases (0.79%). Conversion to laparotomy was required in 3.97% cases. Factors that influenced the rate of conversion included: age>60 years, acute cholecystitis, coexisting diseases, ASA grade III/IV and inexperienced surgeon (p-value .000). Total complication rate was 3.56%, morbidity being 3.17% and mortality 0.39%.Conclusion: Laparoscopic cholecystectomy offers shorter hospital stay and low morbidity/ mortality. The operative time is short and procedure is standard, safe and effective method both for uncomplicated and complicated cholelithiasis. Keywords: Laproscopic, cholecystectomy, safety, complications, conversion, morbidity, mortality